Influence of oral comprehensive nursing intervention on mechanically ventilated patients in ICU: a randimized controlled study - Shengxia Lei; Yan Liu; Enkun Zhang; Chuanxia Liu; Jing Wang; Lingling Yang; Ping Zhang; Ying Shi; Xiaomin Sheng (BMC, 2023)
Abstract Objective To explore the effect of oral comprehensive nursing intervention on mechanically ventilated patients in ICU. Methods Select 76 cases of mechanically ventilated patients in severe ICU admitted to our hospital from January 2022 to October 2022 as the research objects, and divide them into the control group and the observation group according to the way the patients receive oral care. 38 cases each. The patients in the control group received routine nursing intervention, and the patients in the observation group received comprehensive oral nursing intervention on the basis of the nursing of the control group. The clinical index data, oropharyngeal hygiene, pH value, blood gas analysis index levels, and the occurrence and death of ventilator-associated pneumonia were compared between the two groups of patients. Results The hospitalization time of the two groups was compared (P > 0.05); the mechanical ventilation time and ICU stay time of the observation group were significantly lower than those of the control group (all, P < 0.05); the oral odor scores, The plaque index and soft scale index were significantly lower than those of the control group (all, P < 0.05); the pH value, PaO 2 value, and SpO 2 value of the observation group were significantly lower than those of the control group, and the PaCO 2 value was significantly higher than that of the control group. group (all, P < 0.05); the incidence of VAP in the control group was 55.26%, and the mortality rate was 15.79%, the incidence rate of VAP in the observation group was 21.05%, and the mortality rate was 2.63%, and the incidence rate and mortality rate of VAP in the observation group were significantly lower in the control group (all, P < 0.05). Conclusion The application of nursing intervention can effectively promote the recovery of patients, improve the hygiene of patients' oropharynx, adjust the levels of pH and blood gas-related indicators in patients, and reduce VAP in patients. risk of morbidity and mortality.